Isolated Medial Patellofemoral Ligament Reconstruction for Patellar Instability in Skeletally Immature versus Mature Patients - Gruber, Simone (Orthop J Sports Med, 2020)
OBJECTIVES: Medial patellofemoral ligament (MPFL) reconstruction is the standard of care surgical treatment for recurrent patellar instability. Recurrent patellar instability is common after a first-time dislocation in the skeletally immature population. Adult-type reconstruction techniques are often avoided in skeletally immature patients due to the proximity of the femoral insertion of the MFPL to the distal femoral physis. It is currently unclear how outcomes of MPFL reconstruction in skeletally immature patients compare to those for skeletally mature patients. The objective of this study is to present the outcomes of isolated MPFL reconstruction in skeletally immature patients and compare their findings to a skeletally mature population. METHODS: Patients were identified from an institutional patellofemoral registry who underwent isolated MPFL reconstruction from March 2014 to July 2018. Demographic, radiographic, and knee-specific patient-reported outcome measures (PROMs) were collected prior to surgery. Follow-up data collection included knee surveys collected at 1 and 2-years following MPFL reconstruction. Additionally, return to sport rates and episodes of re-dislocations were also collected. Comparisons of demographic and clinical data were made between skeletally immature and mature patients. Sub-analysis was performed on outcomes in skeletally immature patients who underwent MPFL reconstruction where the graft was placed distal to the physis to avoid the growth plate versus those who had standard placement of the graft. Baseline factors were analyzed using independent samples t-tests or chi-square analysis. Longitudinal analysis of knee PROMs was conducted using generalized estimating equation (GEE) modeling. Statistical significance was defined as p-values of 0.05 or less. RESULTS: The study cohort included 107 patients (25 skeletally immature, 82 skeletally mature). Mean age of the study groups was 13.8 years in the immature group (range 11-15) and 21.3 in the mature group (range 14-34). No differences in sex (72% female in both groups) or obesity (0% vs. 8%) was observed between immature and mature patients. Radiographic measures of Caton-Deschamps Index (1.18 in both groups), TT-TG (14.9 vs. 14.8), and Dejour classification (P=0.328) also saw no differences between groups. Longitudinal outcomes in KOOS QoL, IKDC, KOOS PS, and Kujala surveys found no differences between immature versus mature patients over time. However, higher PediFABS was observed in the immature group versus mature at baseline (21.6 vs. 11.9, P<0.001), 1-year (18.1 vs. 11.5, P=0.006), and 2-years (22.4 vs. 11.5, P=0.003). Low incidence of post-operative dislocation and a high return to sport rate was observed in both skeletally immature and mature patients. No statistical differences were observed in all outcomes between immature patients who had standard graft placement and those where the graft was placed distal to the physis. CONCLUSION: Controversy exists in how best to treat the skeletally immature patient with recurrent lateral patellar instability. Due to the risk of injury to the growth plate, many believe it is best to wait to stabilize these patients until they have stopped growing. However, given the high risk of cartilage injury with each dislocation and the long term sequelae of such injuries in these young knees, the risk of waiting may be high. This study demonstrates similar outcomes and recurrence rates in skeletally immature patients with those seen in the mature population without disturbance or injury to the growth plates.